Thin Wires and Edge Imaging Using Hard Bremsstrahlung Generated by a Microfocal Target of a Betatron; Journal of Nondestructive Evaluation; Vol. 41, iss. 1 - Rychkov M. M. Maksim Mikhailovich (2022, 2022)
Title screen